Evaluating the added value of blockchains to local energy markets—Comparing the performance of blockchain‐based and centralised implementations. Issue 4 (7th February 2022) - Zade, Michel; Feroce, Marcello; Guridi, Arturo; Lumpp, Sebastian Dirk; Tzscheutschler, Peter
Abstract: The continuous decentralisation of the energy system due to the expansion of renewable energies requires new coordination mechanisms such as Local Energy Markets (LEMs) that are capable of integrating millions of prosumers as active participants. Since the end of the 2010s, the blockchain technology has been discussed as a potential infrastructure for LEMs and as a potential game‐changer in the energy industry. In this work, the authors introduce LEM specific technology‐independent infrastructure requirements, present a Solidity and Python toolbox that allows to compute a comparative performance analysis between a blockchain‐based and a central LEM and evaluate the added value of a blockchain‐based implementation compared to a conventional reference implementation. Simulations of a LEM with a periodic double auction and settlement showed that a blockchain‐based LEM operation requires more than 140 times the computation time compared to a centralised implementation and cannot fulfil data security requirements. Thus, the authors find that blockchain technology in its current state of development does not add significant value to LEMs. All implemented programmes are published in the open‐source project lemlab as part of the research project RegHEE .